The image of Augustus in the reign of his successors - Cosme, Pierre (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
Augustus had taken care to forge the image by which he wanted posterity to remember him, not only in the form of his instructions for his funeral and for the government of the empire but also in his Res gestae. Until the reign of Nero, the Julio-Claudian emperors claimed their kinship to Au-gustus, because bearing the blood of the founder of the Principality legitimized their power. Star-ting from the Vespasian’s rise to power, princes claimed their kinship to Augustus was behaviou-ral, especially when they set out to found a dy-nasty. Under the tetrarchical regime, the nickna-me Augustus became the equivalent of a military rank, expressing the precedence of the oldest em-perors over those whom they chose as successors and who they nicknamed Caesar. Although the Augustus reference fades under certain reigns, it subsisted under Trajan or Septimius Severus, even after the conversion of Constantine to Christianity, thus revealing its very great flexibility.Mots-clésEmpire romain, ville de Rome, culte impérial, Té-trarchie, Constantin, Théodose Ier, Virgile, Tacite, Pline le Jeune.Key wordsRoman Empire, city of Rome, imperial cult, Tetrar-chy, Constantine, Theodosius, Virgil, Tacitus, Pliny the Younger.MonográficoL’ image d’ Auguste sous le règne de ses successeurs